The Impact of Preintubation Noninvasive Ventilation on Outcomes in Pediatric Acute Respiratory Distress Syndrome - Kopp, Whitney; Gedeit, Rainer G; Asaro, Lisa A; McLaughlin, Gwenn E; Wypij, David; Curley, Martha A Q (Critical care medicine, 2021)
There is evidence that noninvasive ventilation decreases the need for invasive mechanical ventilation. However, children with pediatric acute respiratory distress syndrome who fail noninvasive ventilation may have worse outcomes than those who are intubated without exposure to noninvasive ventilation. Our objective was to evaluate the impact of preintubation noninvasive ventilation on children with pediatric acute respiratory distress syndrome. Secondary analysis of data from the Randomized Evaluation of Sedation Titration for Respiratory Failure trial. Thirty-one PICUs in the United States. Children 2 weeks to 17 years old with pediatric acute respiratory distress syndrome receiving invasive mechanical ventilation, excluding those admitted with tracheostomies. None. Of 2,427 subjects receiving invasive mechanical ventilation, preintubation noninvasive ventilation was used in 995 (41%). Compared with subjects without preintubation noninvasive ventilation use, subjects with preintubation noninvasive ventilation use were more likely to have a history of seizures (10% vs 8%; p = 0.04) or cancer (11% vs 6%; p < 0.001) and have moderate or severe pediatric acute respiratory distress syndrome by the end of their first full day of invasive mechanical ventilation (68% vs 60%; p < 0.001). Adjusting for age, severity of illness on PICU admission, and baseline functional status, preintubation noninvasive ventilation use resulted in longer invasive mechanical ventilation duration (median 7.0 vs 6.0 d), longer PICU (10.8 vs 8.9 d), and hospital (17 vs 14 d) lengths of stay, and higher 28-day (5% vs 4%) and 90-day (8% vs 5%) inhospital mortalities (all comparisons p < 0.001). Longer duration of noninvasive ventilation before intubation was associated with worse outcomes. In children with pediatric acute respiratory distress syndrome, preintubation noninvasive ventilation use is associated with worse outcomes when compared with no preintubation noninvasive ventilation use. These data can be used to inform the design of clinical studies to evaluate best noninvasive ventilation practices in children with pediatric acute respiratory distress syndrome.